High-Titre Neutralizing Antibodies to H1N1 Influenza Virus after Mouse Immunization with Yeast Expressed H1 Antigen: A Promising Influenza Vaccine Candidate - Edyta Kopera; Konrad Zdanowski; Karolina Uranowska; Piotr Kosson; Violetta Sączyńska; Katarzyna Florys; Bogusław Szewczyk (Journal of Immunology Research)
H1N1 influenza virus is still regarded as a serious pandemic threat. The most effective method of protection against influenza virus and the way to reduce the risk of epidemic or pandemic spread is vaccination. Influenza vaccine manufactured in a traditional way, though well developed, has some drawbacks and limitations which have stimulated interest in developing alternative approaches. In this study, we demonstrate that the recombinant H1 vaccine based on the hydrophilic haemagglutinin (HA) domain and produced in the yeast system elicited high titres of serum haemagglutination-inhibiting antibodies in mice. Transmission electron microscopy showed that H1 antigen oligomerizes into functional higher molecular forms similar to rosette-like structures. Analysis of the N-linked glycans using mass spectrometry revealed that the H1 protein is glycosylated at the same sites as the native HA. The recombinant antigen was secreted into a culture medium reaching approximately 10 mg/l. These results suggest that H1 produced in Pichia pastoris can be considered as the vaccine candidate against H1N1 virus.